Effect of Storage Temperature on Key Functions of Cultured Retinal Pigment Epithelial Cells. (13th September 2015) - Pasovic, Lara; Eidet, Jon Roger; Brusletto, Berit S.; Lyberg, Torstein; Utheim, Tor P.
Abstract : Purpose . Replacement of the diseased retinal pigment epithelium (RPE) with cells capable of performing the specialized functions of the RPE is the aim of cell replacement therapy for treatment of macular degenerative diseases. A storage method for RPE is likely to become a prerequisite for the establishment of such treatment. Herein, we analyze the effect of storage temperature on key functions of cultured RPE cells. Methods . Cultured ARPE-19 cells were stored in Minimum Essential Medium at 4°C, 16°C, and 37°C for seven days. Total RNA was isolated and the gene expression profile was determined using DNA microarrays. Comparison of the microarray expression values with qRT-PCR analysis of selected genes validated the results. Results . Expression levels of several key genes involved in phagocytosis, pigment synthesis, the visual cycle, adherens, and tight junctions, and glucose and ion transport were maintained close to control levels in cultures stored at 4°C and 16°C. Cultures stored at 37°C displayed regulational changes in a larger subset of genes related to phagocytosis, adherens, and tight junctions. Conclusion . RPE cultures stored at 4°C and 16°C for one week are capable of maintaining the expression levels of genes important for key RPE functions close to control levels.